Trust in Government as a Factor Influencing Acceptance of Behavioural Public Policy Instruments: Example of Poland and Selected Countries - Danuta Miłaszewicz (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie)
Objective: To assess public support of selected nations with regard to various types of nudges introduced by behavioural public policy and the level of trust these nations have in their governments as the creators of these policies.